A Comparison of Iran’s and Turkey’s Media Diplomacy in the Post-Saddam Iraq - Mansour Rahmani; Ali Shamsabadi (رهیافتهای سیاسی و بین المللی)
Falling out of Saddam Hussain’s dictatorship, gave the opportunity for freedom of speechand media and subsequently the chance to Iran and Turkey to attract Iraqis public opinion.In such context, Media Diplomacy turned into a widely used tool for both Islamic Republicof Iran and AK Party to induce the mutual neighbor country’s political trends in the way thatthey desired. Te Main Question in this article is: What are advantages of Iran and TurkeyMedia Diplomacy in Iraq in comparison to each other? For fnding the answer, we havedescribed the Media and think-tank contents and other related library sources, and aferthat analyzed the methods of Iran and Turkey Media Diplomacy in Iraq from 2003 to 2018and eventually compared the two states’ methods. Regarding to methodology, this article ismainly based on Descriptive-Explanative method. At the last part of the article, we illustratedsimilarities and diﬀerences in Iran and Turkey Media Diplomacy towards Iraq and concluded Iran has the upper hand in Broadcasting, while Turkey is more successful in Entertainment Programs.